MENGGALI BATAS LEVERAGE: ANALISIS STRUKTUR MODAL, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN PROFITABILITAS DI SEKTOR FOOD & BEVERAGES INDONESIA (2020–2024) - Anang S; Muhammad Rahmat (Jurnal Administrasi Profesional, 2026)
This study aims to examine the effect of capital structure on profitability with firm size and sales growth as control variables in food and beverage companies listed on the Indonesia Stock Exchange (IDX). Profitability is measured by return on equity (ROE), while capital structure is proxied by the debt to equity ratio (DER) and debt to asset ratio (DAR). Firm size is measured using the natural logarithm of total assets and sales growth is expressed as annual percentage growth. The sample consists of 15 firms observed over the 2020–2024 period (75 firm-year observations), selected using purposive sampling. The data are analysed using panel data regression in EViews. Based on the Chow test and Hausman test, the fixed effect model is identified as the most appropriate specification. The empirical results show that DER and DAR do not have a statistically significant effect on ROE, nor does firm size. In contrast, sales growth has a positive effect with weak significance (around the 10% level), indicating that higher sales growth tends to increase ROE, although its statistical strength is limited. Jointly, the model including DER, DAR, firm size, sales growth, and firm fixed effects is significant, with an R² of approximately 0.81. These findings imply that, in the context of IDX-listed food and beverage companies during 2020–2024, equity profitability is more strongly driven by firm-specific characteristics and sales dynamics than by variations in capital structure within a relatively moderate leverage range.